2013
DOI: 10.1155/2013/263602
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Calcium Hydroxyapatite and Dextranomer/Hyaluronic Acid for the Endoscopic Treatment of Vesicoureteral Reflux

Abstract: Purpose. Minimal data exists comparing dextranomer/hyaluronic acid (Dx/HA) and calcium hydroxyapatite (CaHA) for the endoscopic treatment of VUR in the hands of a single user. Materials and Methods. We reviewed our consecutive single-user case series of 27 children (42 ureters) receiving endoscopic treatment with CaHA and 21 children (33 ureters) who received Dx/HA injection. Children receiving CaHA injections were divided into two groups of 13 and 14 patients (Coaptite I and II) to assess the learning curve e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Only few studies are available in the literature and reported success rates are widely variable. 20,21 Further studies with larger cohorts and longer followup are needed.…”
Section: Bulking Agentsmentioning
confidence: 99%
“…Only few studies are available in the literature and reported success rates are widely variable. 20,21 Further studies with larger cohorts and longer followup are needed.…”
Section: Bulking Agentsmentioning
confidence: 99%